Pyrroloquinoline Quinone Administration Alleviates Allergic Airway Inflammation in Mice by Regulating the JAK-STAT Signaling Pathway - Zhihui Min; Jiebai Zhou; Ruolin Mao; Bo Cui; Yunfeng Cheng; Zhihong Chen (Mediators of Inflammation)
The current asthma therapies are inadequate for many patients with severe asthma. Pyrroloquinoline quinone (PQQ) is a naturally-occurring redox cofactor and nutrient that can exert a multitude of physiological effects, including anti-inflammatory and antioxidative effects. We sought to explore the effects of PQQ on allergic airway inflammation and reveal the underlying mechanisms. In vitro, the effects of PQQ on the secretion of epithelial-derived cytokines by house dust mite- (HDM-) incubated 16-HBE cells and on the differentiation potential of CD4+ T cells were investigated. In vivo, PQQ was administered to mice with ovalbumin- (OVA-) induced asthma, and lung pathology and inflammatory cell infiltration were assessed. The changes in T cell subsets and signal transducers and activators of transcription (STATs) were evaluated by flow cytometry. Pretreatment with PQQ significantly decreased HDM-stimulated thymic stromal lymphopoietin (TSLP) production in a dose-dependent manner in 16-HBE cells and inhibited Th2 cell differentiation in vitro. Treatment with PQQ significantly reduced bronchoalveolar lavage fluid (BALF) inflammatory cell counts in the OVA-induced mouse model. PQQ administration also changed the secretion of IFN-γ and IL-4 as well as the percentages of Th1, Th2, Th17, and Treg cells in the peripheral blood and lung tissues, along with inhibition the phosphorylation of STAT1, STAT3, and STAT6 while promoting that of STAT4 in allergic airway inflammation model mice. PQQ can alleviate allergic airway inflammation in mice by improving the immune microenvironment and regulating the JAK-STAT signaling pathway. Our findings suggest that PQQ has great potential as a novel therapeutic agent for inflammatory diseases, including asthma.